Research strategy and programmes, 1998-2003. Volume 1. Volume 2: Project 1. Collaborative research for livestock Development in East and Central Africa. Volume 3: Project 2. Crises mitigation in livestock systems in the greater Horn of Africa: from relief to Development - Ndikumana, J.; Mpiri, D. (International Livestock Research Institute, 1998)
In volume 1 of this document are outlined the main features of the livestock sub-sector in East and Central Africa, brief history of the ASARECA Animal Agriculture Research Network, major achievements of network operational mechanisms, meeting frequency and problems. Discussions on the A-AARNET Research Strategy and Programme. Implementation Procedures, Management and Partners, monitoring and evaluation and budget comprises the rest of the document. Volume 2 outlines main features of the livestock sub-sector in East and Central Africa, problems, linkages with European Union, project formulation process, and documentation available. The rest of the document highlights project objectives and expected outputs, project implementaiton, factors ensuring sustainability of impact objectives, economic and financial sustainability and monitoring and evaluation & budget. Volume 3 discusses current crisis mitigation and management activities in the GHA, problems project goal, objectives and expected outputs, approach, implementation steps, implementation procedures, management and partners workplans and budget.